Behavior Modification Strategies for Learners’ Disruptive Behavior - Silyn Mary B. Pasa; Janelle N. Moleňo (Best Practices in Disability-Inclusive Education, 2023)
Behavior issues in the classroom make both the teacher and the learners feel greater pressure, disrupt the lesson's flow, and interfere with both the learning process and the learning objectives. Additionally, they change the structure of the classroom because the distractions caused by disruptive behaviors are now the main emphasis rather than the academic work that is being done. The pilot testing is administered to 3 identified learners with observable disruptive behaviors in class for a span of 3 months. The teacher, the learners, and their connections with one another, as well as the furnishings, the books, and a variety of activities, all play a role in the environment of the classroom and have an impact on how people behave there. With the observed disruptive behaviors of our 3 learners, we decided to use the FBA and BIP as our guide in changing/eliminating the disruptive behaviors associated with our teacher-made behavior management tool. The fact that both the teacher and learners bring experiences and problems from the larger environmental structures within which they exist and operate, such as the rest of the school community, home, family, community, and the wider world, adds to the complexity. A classroom behavior issue might not be resolved by just focusing interventions on learners. This may redirect attention away from a detailed evaluation of the environment of the classroom, the larger school, the home, and community surroundings in which the school is embedded.